Aristolochic Acid Induced Suicidal Erythrocyte Death - Abaid Malik; Rosi Bissinger; Salvatrice Calabrò; Caterina Faggio; Kashif Jilani; Florian Lang (Karger Publishers, 2014)
Background/Aims: Aristolochic Acid, a component of Aristolochia plants, has been shown to cause acute kidney injury, renal aristolochic acid nephropathy, Balkan endemic nephropathy, and urothelial carcinoma. Aristolochic acid nephropathy may be associated with severe anemia. The anemia could theoretically be due to stimulation of eryptosis, the suicidal death of erythrocytes characterized by cell shrinkage and cell membrane scrambling with translocation of phosphatidylserine to the erythrocyte cell membrane surface. Signalling involved in the stimulation of eryptosis include increase of cytosolic Ca2+-activity ([Ca2+]i) and formation of ceramide. Methods: Cell volume was estimated from forward scatter, phosphatidylserine-exposure from annexin V binding, [Ca2+]i from Fluo3 fluorescence, and ceramide abundance from binding of fluorescent antibodies in flow cytometry. Results: A 48 hours exposure to Aristolochic Acid (≥ 75 g/ml) was followed by a significant decrease of forward scatter and increase of annexin-V-binding. The effects were paralleled by a significant increase of [Ca2+]i and significantly blunted, but not abrogated by removal of extracellular Ca2+. Aristolochic Acid further significantly increased ceramide abundance. Conclusions: Aristolochic Acid triggers eryptosis, an effect at least in part due to entry of extracellular Ca2+ and ceramide formation. i 2014 S. Karger AG, Basel